Factors affecting households' decisions in biogas technology adoption, the case of Ofla and Mecha Districts, northern Ethiopia - Mengistu, Mulu Getachew; Simane, Belay; Eshete, Getachew; Workneh, Tilahun Seyoum (Renewable energy, 2016)
This study examined the factors that influence households' decisions on adoption of biogas technology in northern Ethiopia. It involved 179 biogas-user and 179 non-user sample households. They were selected using proportionate simple random and purposive sampling techniques, respectively. Data were collected mainly using semi-structured questionnaires. Data analyses employed logistic regression model. The results of the study showed that male-headed households are more likely to adopt the technology than female-headed ones. Educational level, heads of cattle, income level, access to credit, distance to the main fuelwood source, and number of planted trees have significant (p < 0.01) positive influences on adoption of biogas technology. Significant (p < 0.01) spatial variations are also obtained between the two study sites. Furthermore, the interaction effects of a few pairs of explanatory variables were found significant (p < 0.1). Empowering females and female-headed households, improving educational levels of the household heads, increasing cattle size, raising income levels, improving access to credit, and encouraging households to plant more trees are likely to be some of the way forward to increase the adoption of the technology. Considering the spatial variations, ensuring the creation of satisfied biogas-users, upgrading the existing biogas model through addition of ‘injera’ stove can also enhance adoption of biogas technology. •Male-headed households are more likely to adopt biogas than the female-headed ones.•Education, cattle size, income, and credit are also among the significant factors.•Distance to fuelwood source and number of planted trees are too significant factors.•Upgrading the biogas model to include injera stove can still enhance adoption.•The interaction effects of a few pairs of explanatory variables are found significant.